Productive efficieancy of chlorella vulgaris in nutritional and energy source conditions for use in bioremediation processes - Alexander Pérez Cordero,; Donicer E.Montes Vergara,; Yelitza Aguas Mendoza, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The aim of the present study was to evaluate in vitro the production of proteins from the microalga Chlorella vulgaris by enriching the culture medium with different organic nitrogen sources and light types. The selection of organic nitrogen sources with which the medium was enriched was carried out and the growth of the culture, microalgal biomass productivity and Chlorella vulgaris protein production were evaluatedin different types of light (sunlight, red, white and blue). The samples were monitored for 35 days maintaining the temperature range of 20 to 25 °. The results indicate that the concentration, the type of light and the combination of both have an impact on the growth and protein production of the microalga Chlorella vulgaris. The highest production of wet protein (PH-BH), from the microalgal biomass of Chlorella vulgaris was obtained when molasses was used as a protein source in the presence of wavelength (white light and sunlight) and lower for wavelength (blue light).